The cell : A Molecular Approach - Geoffrey M Cooper (ASM Press ; Sunderland, Mass. : Sinauer Associates, 2009)
Cell presents current comprehensive science in a readable and cohesive text that students can master in the course of one semester. This new edition retains the overall organization, themes, and special features of the Fourth Edition, including Key Experiment and Molecular Medicine essays, chapter sidebars that highlight areas of interest and clinical applications, and end-of-chapter questions with answers at the back of the book